Sosialisasi Ekonomi Sirkular Berbasis Lahan Basah di Kabutapen Banjar Provinsi Kalimantan Selatan - Syahrial Shaddiq; Muhammad Ihsanul Arief; Susi Apriana; Ayu Oktaviani; Novika Rosari; Kasyful Anwar; , Erlan Titoe; Steven Kenli (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity aims to increase public understanding of the circular economy concept and encourage its implementation in utilizing wetland potential in Banjar Regency, South Kalimantan. The outreach program was successfully conducted in Guntung Ujung Village, Gambut District, Banjar Regency on August 29, 2025. The results of this activity indicated an increase in the community's initial understanding of the concept and benefits of a circular economy. More than 50 participants, consisting of village residents, MSMEs, and village officials, attended the activity. Most participants expressed their readiness to apply circular economy principles in their economic activities. New initiatives, such as the processing of rice straw into compost by a farmer group, and the interest of a village women's group in developing purun and water hyacinth crafts, were identified. Based on the evaluation results, the team also identified challenges faced by residents, such as limited access to capital, a lack of understanding of wetland resource management, and a lack of supporting infrastructure. Therefore, the results of the circular economy outreach program will serve as the basis for further programs such as training and mentoring in assisted villages.